Enhanced Structural Stability and Improved Electrochemical Performance of Layered Lithium-Rich Cathode Materials via Tellurium Doping. Issue 12 (1st January 2017) - Meng, Junxia; Wang, Zicheng; Xu, Lishuang; Xu, Huaizhe; Zhang, Shichao; Yan, Qiqi
Abstract : A series of cathode materials Li1.2 [Mn0.56 Ni0.16 Co0.08 ]1- x Te x O2 ( x = 0, 0.02, 0.05 and 0.1) were synthesized via co-precipitation. Structural characterization revealed that these Te-doped materials are of a high ordered layer structure with a low level of cation mixing. The electrochemical experiments showed that the Li1.2 [Mn0.56 Ni0.16 Co0.08 ]0.95 Te0.05 O2 sample (denoted as LRMO-Te0.05 ) delivers a high initial coulombic efficiency of 88.2% with an initial discharge capacity of 271.6 mAh g −1 at room temperature, an enhanced rate capability of 156.1 mAh g −1 at 5 C, and an excellent cycling stability with an initial capacity of 84.3% after 100 cycles. The outstanding electrochemical properties of Te-doped electrodes can be mainly attributed to the enhanced layered structural stability and low charge transfer resistance as a result of substitution of transition metals by Te 6+ . More importantly, voltage decay of the Li1.2 [Mn0.56 Ni0.16 Co0.08 ]1- x Te x O2 ( x = 0, 0.02, 0.05 and 0.1) materials upon cycling can be effectively restrained by manipulating the charge voltage pattern.